Herbivory by the Caribbean king crab on coral patch reefs - Mark J. Butler; Angela M. Mojica (Marine Biology, 2012)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Setbacks to shoot growth are common in woody plants, so how are shoots of some species safer than others? - Don W. Butler; Sean M. Gleason; Mark Westoby (Ecology, 2012)
Tissue turnover is a critical facet of plant life history variation. This study quantifies losses from setbacks to growth of terminal woody shoots 1.2 m long, across 83 species and seven sites in eastern Australia. Setbacks, where the leading meristem had been removed or died and a new leader had emerged, were common (median three per shoot). Shoots had lost an average of 0.25 m of lead‐stem length for 1.2 m net shoot‐length gain. Insects like girdlers and borers were prominent causes of large setbacks. The sites spanned tropical to temperate and humid to semiarid climates, but variation in stem loss was much greater across species than across sites. We measured 17 plant functional traits related to growth form, mechanics, hydraulics, and economics. Only four traits were correlated with variation across species in stem losses: stem diameter, stem nitrogen content, bark thickness, and maximum photosynthetic rate. The correlations were weak. Stem specific gravity (wood density) showed no correlation with risk. Our results suggest a pattern similar to the growth–risk trade‐off known for herbaceous plants, where traits associated with fast growth increase tissue turnover and herbivory, but the weak correlations leave ample scope for other influences that remain to be identified.